La dynamique du peuplement et des espaces agraires médiévaux en Berry : propositions pour une évaluation de l’opportunisme des sociétés anciennes - Nicolas Poirier (Archéologie Médiévale)
The advantage of studying long term population processes of agrarian spaces, is being able to asses the part of inheritance that profits each population phase. The notions of opportunism or innovation in the choices made by ancient societies relative to the establishment of settlements or farmed spaces are rarely considered. We thus propose two indicators for the estimation of the opportunism of Medieval societies which, combined with reconstitution of the environmental context, partly explain the different episodes of taking and reliquishing hold of spaces, or the mobility within population patterns and parishes during the Middle Ages.